Effects of In-plane elastic stress and normal external stress on viscoelastic thin film stability - Closa, Fabien; Ziebert, Falko; Raphaël, Elie (Mathematical modelling of natural phenomena, 2012)
Motivated by recent experiments on the electro-hydrodynamic instability of spin-cast polymer films, we study the undulation instability of a thin viscoelastic polymer film under in-plane stress and in the presence of either a close by contactor or an electric field, both inducing a normal stress on the film surface. We find that the in-plane stress affects both the typical timescale of the instability and the unstable wavelengths. The film stability is also sensitive to the boundary conditions used at the film-substrate interface. We have considered two conditions, either rigidly attaching the film to the substrate or allowing for slip.
Gesehen am 27.09.2022